Simulation of fluid suspended particle behaviour subject to transverse standing acoustic fields - Dabic, Mihajlo (Department of Chemical Engineering, 2015)
The computational study addressed the effectiveness with which a standing wave acoustic field could be used to deflect quartz particles carried in water at 20°C through a simple parallelepiped control volume representative of a vertically orientated duct geometry dimensioned 50 × 50 × 70 cm 3 , with square base. An acoustically driven planar standing wave field produces quasi-static oscillatory pressure gradients within resonant cavities, which are responsible for acoustic forces, which act on particles, located within the acoustic field. These forces drive particles to nodal (no fluctuation) or anti-nodal (continuous fluctuation) planes of pressure. Standing wave fields are generally produced by a transducer driving into a fluid through an adhesively bonded matching layer. The wave is reflected at the opposite boundary layer terminating in an air backing. The chamber is dimensioned so as to produce constructive wave interference between the two waves travelling in opposite directions. The acoustic force has been used in small scale filtration systems to deflect particles and on larger scales as a pre filtration agglomerator clumping very small particles which are otherwise poorly filtered in isolation by conventional methods. The study was twofold, in that a major component of the study comprised developing the architecture of the computational model, the other part comprising qualitative model validation through parameter variation. The study involved coupling between Computational Fluid Dynamics (CFD) Software (OpenFOAM) and Discrete Element Modelling (DEM) Software (LIGGGHTS), through a coupling code (CFDEM) built as an extension to OpenFOAM and tailored for LIGGGHTS. The acoustic field was assumed ideal i.e. in a lossless medium with perfect reflection at the opposite wall. Particle-particle and particle-wall collisions were circumvented by using larger time increments, inadequate to resolve col- lisions, and inserting particles in the bulk of the flow away from any wall boundary. Twenty particles with uniform radial size distribution in the range 5-30 micron were seeded in the flow field about 10 cm from the bottom inlet, and carried in the z direction at various flow speeds, 0.1 ms − 1 , 0.5 ms − 1 and 1 ms − 1 , whilst being subject to acoustic forces in the x direction, to investigate deflection response and transducer lengths required to achieve adequate lateral deflection. The model accounted for drag, buoyancy, gravity and primary acoustic forces. Flow velocities distinguished by those maxi mum velocities recorded at duct centrelines were obtained by adjusting pressure gradients across the domain. The fluid continuum was modelled through Reynolds Averaged Navier Stokes (RANS) equa- tions, supplemented by an eddy viscosity k − two equation turbulence model. The flow profile was validated against the analytic Darcy-Weisbach pressure to mean velocity relation. Two acoustic driv- ing frequencies, 14794 Hz and 26629 Hz , were investigated for each flow rate to determine the effect frequency had on acoustic force magnitude, nodal distribution and particle residence time. Acoustic deflection efficiency was measured as that time or particle vertical travel length required, coinciding with a lateral deflection to within 1.5 mm of an adjacent nodal plane. From a computational point of interest acoustic force dependencies and trends were qualitatively evaluated for consistency with theoretic equations and published literature